The impact of tourism on farmers’ household income in the context of China’s regulatory policies of protected areas - He, Dan; Wang, Jingwen; Zhang, Tingting; Xu, Zhe; Wang, Yang; Liu, Shiyu; Chen, Ke (Frontiers in Forests and Global Change, 2023)
China’s central government has issued several governance policies for protected areas since 2015. Some of these affected the use of natural resources by the farmers living in protected areas. Tourism is an important source of income for farmers around such areas. Based on the survey data of 1,028 farmer households, this study use propensity score matching (PSM) method to solve the samples selection bias and improve the accuracy of evaluation .For both the vertical and horizontal, this study explores the changes in the impact of tourism on farmers’ household income under regulatory policies. Longitudinally, before the introduction of these policies, the income effect of tourism on the per capita net income of households was about 49.21%, while this percentage dropped to 41.36% after their introduction. Horizontally, before these policies were implemented, the farmers involved in the protected areas’ tourism experienced a 16.30% higher tourism income effect than those outside protected areas. Post implementation, the income effect of tourism in protected areas dropped by 9.83%. Empirical data based on the abovementioned were used to verify the inhibitory effect of the existing control policies on tourism in protected areas, and put forward the direction of policies reform in China or state governaned-protected areas in other countries.